Development of a loop-mediated isothermal amplification detection assay for Dictyocaulus viviparus (Bloch, 1782) lungworm: DviLAMP - Nak-on, Sirapat; Campbell, Paul; Shalaby, Maha Mansour; McIntyre, Jennifer; Antonopoulos, Alistair; Chontananarth, Thapana; Laing, Roz (Frontiers in Veterinary Science, 2024)
The bovine lungworm, Dictyocaulus viviparus (Bloch, 1782), is highly pathogenic and disease outbreaks can be difficult to predict and manage. Rapid and accurate diagnosis is vital, but without a sensitive diagnostic test this remains challenging in clinical practice. High performance molecular detection tools are therefore required to improve the diagnosis of this parasite and promote the implementation of strategic control measures. Loop-mediated isothermal amplification (LAMP), a rapid DNA assay, offers potential for field-based detection. Here we report a novel LAMP assay (DviLAMP), that was designed to target the D. viviparus internal transcribed spacer 2 (ITS2) ribosomal DNA region. Firstly, genomic DNA was extracted from a single D. viviparus L1 larva to amplify and clone the ITS2 into the recombinant plasmid (DviITS2). The DviLAMP successfully detected the target, with results shown by gel electrophoresis and real-time analysis, in addition to point-of-care amenable end-point detection: colorimetry and lateral flow dipstick (LFD). Analytical sensitivity can detect 0.5 ng DviITS2 following 45 min of incubation at 64°C, increasing to just 1 pg following 90 min of incubation. Using the same primers, other nematodes of cattle, Ostertagia ostertagi and Cooperia oncophora, were also detectable both by gel electrophoresis and real-time. However, when FITC and biotin tagged primers were incorporated to adapt the DviLAMP to LFD end-point detection, the LFD showed specific detection of D. viviparus. Further development of DviLAMP as a point-of-care test could significantly improve the sensitivity of lungworm diagnosis in the field.